Non-formal education in university museums linked to Geosciences in Paraná. e2421428 - Camila Priotto Mendes; Antonio Liccardo; Carla Silvia Pimentel (Terr@ Plural)
this paper presents an overview of non-formal education in Paraná university museums linked to geosciences. These museums exhibit in their collection contents such as Archaeology, Astronomy, Botany, Geology, Meteorite, Mineralogy, Paleontology, Pedology, Water Resources and Zoology. The identification and selection of the museums that are part of this research was carried out in 2020 on the Museusbr platform (website belonging to IBRAM) and on the website of the Coordination of the State Museum System (COSEM), linked to the Secretariat of Social Communication and Culture of the State of Paraná. In 328 museums and similar spaces located in Paraná, seven of them are linked to universities and correspond to this thematic section of research. From this survey, the general directors of each institution were interviewed and the data analyzed indicated that these museums are mainly fostered by resources from universities; which often promote activities beyond guided and non-guided tours, such as itinerant shows, workshops, short courses and events, and generally make available to the public some didactic material to enrich the visitation experience, folders, pamphlets, scientific object kits and replicas. The data also demonstrated that the professionals of educational actions and mediators have specific training in the thematic areas of museums and are fundamental for the evaluation of the experience of visitors. The perception of mediators has been the main source of information to support adjustments in education strategies in museums. Social networks play an important role in most of the museums consulted, as an instrument for the dissemination of the museum and its educational actions. In general terms, the university museums of Paraná consulted promote non-formal education actions in accordance with the National Museal Education Policy proposed by IBRAM.